Faktor- Faktor yang Mempengaruhi Depresi Anak Usia Sekolah: Kajian Literatur - Iga Ayu Saputri; Artika Nurrahima (Master of Nursing, Faculty of Medicine, Universitas Diponegoro, Indonesia, 2020)
Introduction: School-age children are a vulnerable group who have a high risk of experiencing psychosocial problems, one of which is depression. School-age children who experience depression have adverse effects, such as increasing the risk of committing suicide, being dragged into bad habits, and falling into alcohol abuse, or other drugs as a way to calm down to feel better. Depression is caused by several factors, by knowing these factors can be done to prevent depression in school-age children, so that the incidence of depression in school-age children can be minimized. This study aims to determine the factors that influence depression in school-age children.Methods: The method used in this research is the study of literature. Researchers reviewed 10 articles sourced from Google Scholar, Science Direct, and Springer Link with keywords risk factor, depression, and school-age children.Results: The results of the literature study indicate that the factors that influence depression in school-age children, namely the pressure experienced every day, the school environment, family environment, family finances, maternal depression, premature, and emotional intelligence.Conclusion: Further quantitative research on the factors that influence depression can provide a real picture of the causes of depression in school-aged children in Indonesia.